Visual Evoked Potential Recording in a Fatigued and Drowsy Patient under Anti-Seizure Medicine Treatment - Shushtarian, Seyed Mohammad Masoud; Pour Mazar, Reza; Fadaeifard, Shahed (Journal of Ophthalmic and Optometric Sciences, 2021)
The visual evoked potential is an electrophysiological technique to screen visual pathway disturbances. A quite fatigued and drowsy patient due to anti-epileptic drug therapy suffering from diplopia was tested for visual evoked potential with pattern reversal stimulation. The result was not reliable; thus, flash stimulation was applied. The optimal result was obtained considering both types of stimulations.